2022
DOI: 10.1002/eat.23854
|View full text |Cite
|
Sign up to set email alerts
|

Association of emotion recognition ability and interpersonal emotional competence in anorexia nervosa: A study with a multimodal dynamic task

Abstract: Objective Interpersonal difficulties are evidenced in Anorexia Nervosa (AN) and are thought to contribute to disease onset and maintenance, however, research in the framework of emotional competence is currently limited. Previous studies have often only used static images for emotion recognition tasks, and evidence is lacking on the relationships between performance‐based emotional abilities and self‐reported intra‐ and interpersonal emotional traits. This study aimed to test multimodal dynamic emotion recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…Furthermore, both groups rated angry characters less positively than neutral ones, which in turn were rated less positively than the happy ones. Previous studies reported a similar finding in terms of affective valence judgements, suggesting that individuals with AN, despite experiencing difficulties in emotion recognition (Blomberg et al, 2021;Martini et al, 2023), perceive and evaluate affective valence similarly to individuals without AN (De Sampaio et al, 2015). Moreover, affective valence appears to be particularly sensitive to the altered body representation (PC2 "negative body image"), as revealed by the negative relationship.…”
Section: Emotional Stimulisupporting
confidence: 63%
“…Furthermore, both groups rated angry characters less positively than neutral ones, which in turn were rated less positively than the happy ones. Previous studies reported a similar finding in terms of affective valence judgements, suggesting that individuals with AN, despite experiencing difficulties in emotion recognition (Blomberg et al, 2021;Martini et al, 2023), perceive and evaluate affective valence similarly to individuals without AN (De Sampaio et al, 2015). Moreover, affective valence appears to be particularly sensitive to the altered body representation (PC2 "negative body image"), as revealed by the negative relationship.…”
Section: Emotional Stimulisupporting
confidence: 63%
“…This would be consistent with the conceptualization of hyperactivity and pathological eating behaviors as coping mechanisms for excessive anxiety in individuals with EDs [ 15 ]. Further studies may deepen the impact of the pandemic on social and emotional skills in patients with ED, given the significant role of these skills in AN [ 38 ].…”
Section: Discussionmentioning
confidence: 99%